Outcomes Assessment: How Much Value Does University Education Add? - Evers, Fredrick T.; Gilbert, Sid N. (Canadian Journal of Higher Education, 1991)
Data from two independent research studies are used to assess student outcomes resulting from formal university instruction. University education is found to produce added value on a number of important dimensions of student development. However, on a number of other important dimensions of student development much less value is added by formal university courses. The latter educational outcomes, it is argued, represent some of the more crucial characteristics which future university graduates will require.